“It wasn’t just one thing”: A Qualitative Study of Newly Homeless Emergency Department Patients - Doran, Kelly M. (Acad Emerg Med, 2019)
OBJECTIVES: Emergency departments (EDs) frequently care for patients who are homeless or unstably housed. One promising approach taken by the homeless services system is to provide interventions which attempt to prevent homelessness before it occurs. Experts have suggested that health care settings may be ideal locations to identify and intervene with patients at risk for homelessness, yet little is known even about the basic characteristics of patients who might benefit from such interventions. METHODS: We conducted in-depth, one-on-one qualitative interviews with ED patients who had become homeless within the past 6 months. Using a semi-structured interview guide, we asked patients about their pathways into homelessness and what might have prevented them from becoming homeless. Interviews were digitally recorded and professionally transcribed. Transcripts were coded line-by-line by multiple investigators who then met as a group to discuss and refine codes in an iterative fashion. RESULTS: Interviews were completed with 31 patients. Mean interview length was 42 minutes. Four main themes emerged: 1) unique stories yet common social and health contributors to homelessness, 2) personal agency versus larger structural forces, 3) limitations in help from family or friends, and 4) homelessness was not expected. CONCLUSIONS: These findings demonstrate gaps in current homeless prevention services and can help inform future interventions for unstably housed and homeless ED patients. More immediately, the findings provide rich, unique context to the lives of a vulnerable patient population commonly seen in EDs.